Pengaruh pengungkapan emisi karbon dan kinerja keuangan terhadap nilai perusahaan dengan kinerja lingkungan sebagai pemoderasi - Aghitsna Nur Fadiyah; Yongky Rangga Yuda Nugraha (PT Wim Solusi Prima, 2025)
This quantitative research aims to examine the impact of carbon emission disclosure and financial performance on firm value, with environmental performance acting as a moderating variable. The study utilizes secondary data collected from the annual and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange during 2022–2024. Purposive sampling was employed to select 59 companies as the research sample. Panel data analysis was conducted using STATA 14. The findings indicate that carbon emission disclosure does not influence firm value, financial performance has no effect on firm value, environmental performance does not moderate the relationship between carbon emission disclosure and firm value, whereas environmental performance is able to moderate the effect of financial performance on firm value.